Traditions and knowledge of the people from the Jenipapo quilombola community, Caxias, Maranhão (Research, Society and Development, 2022)
The cultural manifestations of a social group can vary in time and space and in the way they are presented, without affecting its identity. The objective of this study was to describe the main social and cultural manifestations of the Jenipapo quilombola community, in the municipality of Caxias, state of Maranhão. The methodological stages were: bibliographic, historiographical and field research through interviews in households. The interface of the cultural experience of the Jenipapo quilombola community was carried out by participant observation. The main cultural manifestations were expressed by different types of dances: the “tambor de Crioula”, “bumba meu boi”, nursery rhymes, “quadrilhas juninas”, and the Lili’s dance, a folkloric expression that portrays the reality of the rural area of the municipality of Caxias. Beliefs and superstitions are also part of the imagination and routine of the people from the quilombo Jenipapo and are closely linked to their relationships with nature. Respecting the phases of the moon in everyday activities is part of this cosmo-vision, and the older residents are the main holders of this knowledge. It was identified that they maintain the respect in towards sacred aspects and saints of the Catholic Church, but they engage in healing and blessing rituals, paying obedience to the “beings of the forest” and “superior entities”. The desire of the residents in maintaining important cultural traditions of Maranhão is noticeable. Despite the technological resources that influence the way of life in the Jenipapo quilombola community, the social actors preserve their traditions and perpetuate the quilombola culture inherited from their enslaved ancestors.